2015
DOI: 10.2147/ott.s74855
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of apoptosis-related gene functional variants in advanced non-small-cell lung cancer patients treated with first-line platinum-based chemotherapy

Abstract: BackgroundSingle-nucleotide polymorphisms in apoptosis-related genes have been shown to play a role in the efficacy of platinum-based chemotherapy and may influence clinical outcomes. Our study aimed to evaluate the correlations of four functional single-nucleotide polymorphisms − FAS −670 A>G, FAS ligand −844 T>C, survivin −31 G>C, and survivin 9386 C>T – with drug response and clinical outcomes in advanced non-small-cell lung cancer patients who received platinum-based chemotherapy.Materials and methodsPolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…Finally the results did not show any association between the investigated polymorphisms and response rate which is consistent with the results shown by Tao et al15 However, Liu et al demonstrated that FASL-844 C>T polymorphism has an influence on NSCLC response to platinum agents 24. However, their conclusion is based on the interaction between this polymorphism and other genetic polymorphisms which is contrary to our study and Tao et al hypothesis where the effect of this polymorphism was studied solely and not as interaction with other genetic polymorphisms.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Finally the results did not show any association between the investigated polymorphisms and response rate which is consistent with the results shown by Tao et al15 However, Liu et al demonstrated that FASL-844 C>T polymorphism has an influence on NSCLC response to platinum agents 24. However, their conclusion is based on the interaction between this polymorphism and other genetic polymorphisms which is contrary to our study and Tao et al hypothesis where the effect of this polymorphism was studied solely and not as interaction with other genetic polymorphisms.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, Tao et al did not find any relationship between this polymorphism and PFS or OS in Chinese NSCLC patients 15. Also, these results were consistent with Park et al and Wu et al who did not observe a prognostic relevance for this polymorphism in Korean and Chinese NSCLC patients, respectively 17,23…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…For example, Javid et al found that survivin -31C/C in lung cancer patients was associated with a poor overall survival rate 41, and Rosato et al showed that the -31 C/C genotype was related to node metastasis and patient survival 36. Moreover, Tao et al showed that survivin 9386 C>T polymorphisms are potential independent prognostic factors in NSCLC patients treated with platinum-based chemotherapy 42. The present study showed that survivin -31C/C was stage-related in patients with EGFR exon 19 mutations.…”
Section: Discussionmentioning
confidence: 99%